2011
DOI: 10.1007/s00436-011-2616-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on animal models for Opisthorchis viverrini infection: host interaction through susceptibility and pathology

Abstract: Syrian hamsters and gerbils are animal models for Opisthorchis viverrini infection. In both models, the parasites develop into adults with different pathologies of the hepatobiliary system. However, no comparative pathological studies have yet been completed. We therefore investigated host interaction through the susceptibility and pathological changes of Syrian hamsters and gerbils infected with 50 O. viverrini metacercariae for 30, 60, and 90 days post-infection. Animals were sacrificed at each time point fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…It has been suggested that the ‘acidification’ of bile through reflux into the low pH of the stomach precipitates inhibitory bile acids, thereby allowing colonization by H. pylori (Hynes et al, 2003; Shao et al, 2008). In case of opisthorchiasis, the infection by the flukes can disturb bile acid composition (Wongpaitoon et al, 1988; Wonkchalee et al, 2012) that may reduce alkalinity of the bile, leading to damage to biliary epithelia and inflammation (Strazzabosco et al 2000). All these phenomena may facilitate conditions that favor colonization by Helicobacter during concurrent infection with liver flukes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the ‘acidification’ of bile through reflux into the low pH of the stomach precipitates inhibitory bile acids, thereby allowing colonization by H. pylori (Hynes et al, 2003; Shao et al, 2008). In case of opisthorchiasis, the infection by the flukes can disturb bile acid composition (Wongpaitoon et al, 1988; Wonkchalee et al, 2012) that may reduce alkalinity of the bile, leading to damage to biliary epithelia and inflammation (Strazzabosco et al 2000). All these phenomena may facilitate conditions that favor colonization by Helicobacter during concurrent infection with liver flukes.…”
Section: Discussionmentioning
confidence: 99%
“…Biliary inflammation has been linked with ulcerative colitis and hence O. viverrini ‐induced perturbations of microbial communities could contribute to inflammation by exposing the cholangiocytes to microbes or metabolites of enteric or parasite‐associated microbes (7, 8) and recruitment of mucosal lymphocytes to the biliary system (69). In addition, perturbations in the microbiota may be responses to bile constitution, since O. viverrini infection affects composition and concentration of bile acids (70, 71). Bile acid composition influences gut microbiota (72) and can promote pathobiont expansion and inflammation (73).…”
Section: Discussionmentioning
confidence: 99%
“…After 24 hr exposure, only live B. siamensis goniomphalos snails from each group (untreated control, camellia-treated, mangosteen-treated, and niclosamide-treated), were processed for analysis of histopathological changes by hematoxylin and eosin staining, following previous reports [22-24]. In brief, B. siamensis goniomphalos snails were fixed with buffered 10% formalin solution for 1 week and then washed with PBS solution for 15 min 3 times.…”
Section: Methodsmentioning
confidence: 99%